Effects of Sequential Teaching Methods on Senior Secondary School Biology Students’ Achievement in Niger State, Nigeria - DAJAL, Robert Goebognaan; APOCHI, Maria Aladi; PAUL-FIASE, Rose Udoo (Ilorin Journal of Education, 2023)
The study investigated the effects of Sequential Teaching Methods on senior secondary school Biology students’ achievement in Niger State, Nigeria. The research design used was quasi-experimental using pre-test and post-test control group approach. Two research questions and two null hypotheses were formulated. The population of the study consisted of 165,034 SSII Biology students in the twenty-five Local Government Areas of Niger State. The sample size consisted of 100 SSII Biology students from two selected senior secondary schools in Tafa Educational Zone. The instruments for data collection were 30-item Biology Achievement Test (BAT) validated by experts. Split half method was used to establish the reliability of BAT and the results obtained gave the reliability coefficient r = 0.85. Descriptive statistics were used to answer the two research questions, while ANCOVA was used to test the null hypotheses. The results of the analysis showed that there was significant difference in students’ academic achievement in Biology between those exposed to sequential teaching methods and their counterparts taught with conventional method. It was also shown that there was no significant difference in students’ academic achievement of male and female taught Biology using sequential teaching methods. The research concluded that sequential teaching method has positive effect on students’ academic achievement and is gender friendly. It was recommended among others that: regular workshops, seminars and conferences should be held for Biology teachers to make them familiar with the knowledge of sequential teaching methods and should be encouraged to use it in their classroom teaching and learning.